Pemberdayaan Santri dalam Upaya meningkatkan Skill Enterpreunership - Syafi'e, Imam (Mabny: Journal of Sharia Management and Business, 2023)
This research explains the empowerment of students in Islamic boarding schools. Islamic boarding schools which are known as places to gain knowledge do not always only discuss religious knowledge, but Islamic boarding schools also train the skills of students for the reason of improving the community's economy in the future. In this case the researcher used a descriptive qualitative research method with data collection methods based on the results of interviews and field observations. The data obtained includes students, internal servants and boarding school administrators. Based on research results at the Bata-bata Pamekasan Islamic Boarding School, the Santri Empowerment program is a positive effort to build and realize the goals of the Islamic boarding school in equipping students with religious and general knowledge. By providing training and improving entrepreneurial skills, this empowerment program aims to encourage students to become more involved in business. By providing students with creative and innovative skills, it is hoped that the student empowerment program will help business growth. This program will encourage students to become entrepreneurs based on human values ​​and not monetary gain.